Electrical discharge machining of titanium alloy using copper tungsten electrode with SiC powder suspension dielectric fluid - Rival, Rival (2005)
Titanium alloys which are categorized as lightweight materials, posses greater strength and toughness are usually known to create major challenges during conventional and non-conventional machining. Electrical discharge machining (EDM) which is very prominent amongst the non-conventional machining methods is expected to be used quite extensively in machining titanium alloys due to the favorable features and advantages that it can offer. This project was undertaken to study the machining performance of EDM and powder mixed dielectric-electrical discharge machining (PMD-EDM) on titanium alloy, Ti-6246 using copper tungsten (CuW) electrode. Silicon carbide (SiC) powder at various concentration was mixed in the dielectric to evaluate its effectiveness during the PMD-EDM process. The effect of varying the machining parameters on the machining responses such as material removal rate (MRR), electrode wear ratio (EWR), surface integrity and overcut was investigated. The experimental plan for both processes were conducted according to the design of experimental (DOE) and the results were statistically evaluated using analysis of variance (ANOVA). Response surface methodology (RSM) was employed in evaluating the machining performance of the PMD-EDM process and mathematical models for MRR, EWR and machined surface roughness (SR) were established. Result showed that current was the most significant parameter that influenced the machining responses on both EDM and PMD-EDM of Ti-6246. It was also found that PMD-EDM process produced less damaging effect on the surface integrity of the machined surface as compared to EDM process.